2022
DOI: 10.1093/plcell/koac207
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide metabolome of germinating Arabidopsis thaliana seeds reveals a central role for thymidine phosphorylation in chloroplast development

Abstract: Thymidylates are generated by several partially overlapping metabolic pathways in different subcellular locations. This interconnectedness complicates an understanding of how thymidylates are formed in vivo. Analyzing a comprehensive collection of mutants and double mutants on the phenotypic and metabolic level, we report the effect of de novo thymidylate synthesis, salvage of thymidine, and conversion of cytidylates to thymidylates on thymidylate homeostasis during seed germination and seedling establishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“… 45 In the process of seed germination, the involvement of purine metabolism in the myriad of bioenergetic processes is required for the mobilization of storage products; moreover, active nucleotide biosynthesis is needed to provide sufficient pyrimidine nucleotides to the embryos to facilitate nucleic acid synthesis. 46 In this study, we observed that some nucleotides (cytosine, CAMP, cytidine, deoxyadenosine and guanosine) involved in the purine metabolism pathway accumulated significantly during the germination of Z. Nitidum seed, consistent with the varying trend of nucleotides during seed germination of common beans, 47 castor, 48 Arabidopsis thaliana 49 and other seeds. This finding indicates that a large number of nucleotides are required for the germination of Z. nitidum seeds in addition to the mobilization of nutrients in cotyledons.…”
Section: Discussionsupporting
confidence: 76%
“… 45 In the process of seed germination, the involvement of purine metabolism in the myriad of bioenergetic processes is required for the mobilization of storage products; moreover, active nucleotide biosynthesis is needed to provide sufficient pyrimidine nucleotides to the embryos to facilitate nucleic acid synthesis. 46 In this study, we observed that some nucleotides (cytosine, CAMP, cytidine, deoxyadenosine and guanosine) involved in the purine metabolism pathway accumulated significantly during the germination of Z. Nitidum seed, consistent with the varying trend of nucleotides during seed germination of common beans, 47 castor, 48 Arabidopsis thaliana 49 and other seeds. This finding indicates that a large number of nucleotides are required for the germination of Z. nitidum seeds in addition to the mobilization of nutrients in cotyledons.…”
Section: Discussionsupporting
confidence: 76%
“…However, in 7‐d‐old A. thaliana plants, the concentrations of IDP and ITP rose significantly when plants were treated with ribavirin. We hypothesize that this discrepancy is due to a different developmental context, as there is likely more overall nucleotide kinase activity in developing tissues than in fully developed leaves (Niehaus et al ., 2022), which would also increase the rate of spurious IMP phosphorylation.…”
Section: Discussionmentioning
confidence: 99%